Telecommunications infrastructure in the Arctic: a circumpolar assessment - Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) (Arctic Council Secretariat, 2017)
From 2015-2017, the TFTIA worked to assemble and assess information about the available telecommunications infrastructure in the Arctic and the present-day needs of users living, working, or traveling in the Arctic. This report presents the Task Force's investigation and analysis, including maps showing the extent of telecommunications coverage in each of the eight Arctic Sates. The report also provides an overview of each State's telecommunications priorities.